Los servicios de interés general en la Unión Europea - Laguna de Paz, José Carlos (2016)
(i) Since the eighties, the European Union has implemented a policy aimed to achieve that the services of general economic interest are truly integrated in the internal market. To this end, European regulation has liberalized and harmonized the legal framework of the main economic sectors. Significant progress towards European integration has been achieved. However, the internal market is still not truly effective. (ii) Conversely, non- economic services are primarily the responsibility of Member States. They are not covered by the internal market rules, although the general provisions of the Treaty are to be applied.